Geographical Analysis For Proposed Dams in Sulaimaniyah Province and Their Impacts on Water Necessary Supply (Raparin Journal of Humanities (RJH), 2022)
The goal of this research is to geographical analysis for revelation of water necessary in Sulaimaniyah governorate for different economic and human sectors in all province districts, and revelation the role and effect of proposed dams on the water supply in Sulaymaniyah. In this research we used inductive method with analysis and comparative methods. The research has got some results, like these: the proposed dams can supply (%72.64) of water necessary for different sectors in sulaymaniyah province, so that the proposed dams will significant role to water supply for sulaymaniya residents. Rainfall fluctuation and decrease ground surface runoff and underground water in Sulaymaniyah now, building proposed dams will necessary in the future, because these dams can collection rain water and decrease using underground water, there for its impacts on decrease water crisis and drought and their can revitalize agriculture sector. In the districts of sulaymaniyah province have differences on water reservoirs in proposed dams comparative with water necessaries. we have differences from district to another, some districts have further water balance, some districts have included water balance border and some districts are in the non-balance group.